2012
DOI: 10.1016/j.cell.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Guidance of Central Memory T Cells Is Critical for Antiviral Recall Responses in Lymph Nodes

Abstract: SUMMARY A defining feature of vertebrate immunity is the acquisition of immunological memory, which confers enhanced protection against pathogens by mechanisms that are incompletely understood. Here, we compared responses by virus-specific naive T cells (TN) and central memory T cells (TCM) to viral antigen challenge in lymph nodes (LNs). In steady-state LNs, both T cell subsets localized in the deep T cell area and interacted similarly with antigen-presenting dendritic cells. However, upon entry of lymph-born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
247
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(271 citation statements)
references
References 64 publications
21
247
3
Order By: Relevance
“…It will be interesting to determine whether a similar process is happening with Plasmodium-specific cells in the liver. Moreover, we do not know which GPCRs are required for further T-cell recruitment and cluster formation; interestingly, it has been demonstrated that both specific and nonspecific T cells are recruited to the site of influenza virus infection in the lungs via CCR5 (27), whereas in the lymph node, CXCL9-CXCR3 interactions have been shown to be critical for the clustering of antigen-specific effector CD8 + T cells around DCs in viral infections (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to determine whether a similar process is happening with Plasmodium-specific cells in the liver. Moreover, we do not know which GPCRs are required for further T-cell recruitment and cluster formation; interestingly, it has been demonstrated that both specific and nonspecific T cells are recruited to the site of influenza virus infection in the lungs via CCR5 (27), whereas in the lymph node, CXCL9-CXCR3 interactions have been shown to be critical for the clustering of antigen-specific effector CD8 + T cells around DCs in viral infections (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…During the anamnestic T cell response to LCMV infection, Sung et al found LN-resident CD8 C memory T cells were first located within the LN T cell zone. Within 8 hours of infection, however, 90% of memory CD8 C T cells relocated to the periphery of the LN, where they facilely eliminated virusinfected cells (22). This peripheral positioning was dependent on expression of the chemokine receptor CXCR3.…”
Section: Lymph Nodementioning
confidence: 99%
“…Examining a third (and actual murine!) virus, lymphocytic choriomeningitis virus (LCMV), Sung et al visualized infected cells in both the LN SCS and medulla, but not in the node's interior, consistent with the exclusion of molecules larger than 70 kDa (22). Viral vaccines (eg.…”
Section: Viral Trafficking To and Infection Of The Lymph Nodementioning
confidence: 99%
“…Compared with primary T cells, memory CD8 + T cells show an increased cell frequency, longevity, improved effector function, and increased responsiveness to lower Ag concentration [19][20][21]. Nonetheless, memory T cells remain dependent on DC for reactivation, reflecting an ongoing requirement for costimulation [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Once established, high expression of CD27 is a feature of cells with a T CM -like phenotype and greater capacity for mounting recall responses compared with CD27 lo cells [14,16]. In contrast, CD27 lo cells are associated with a terminally differentiated/senescent memory T-cell phenotype in both humans and mice [17,18].Compared with primary T cells, memory CD8 + T cells show an increased cell frequency, longevity, improved effector function, and increased responsiveness to lower Ag concentration [19][20][21]. Nonetheless, memory T cells remain dependent on DC for reactivation, reflecting an ongoing requirement for costimulation [22,23].…”
mentioning
confidence: 99%